Pengaruh Media Audiovisual terhadap Tingkat Pengetahuan dan Sikap Cuci Tangan Pakai Sabun (CTPS) yang Baik dan Benar di SD Yaspenhan Medan Marelan - Arifin, Arifin Shaleh Lubis; Nanda, Meutia; Ismah, Zata (Jurnal Kesehatan Komunitas, 2024)
SD Yaspenhan Medan Marelan is still not equipped for hand washing with soap (CTPS) activity facilities such as the absence of soap in the hand washing place and there is no health promotion media in the form of posters or leaflets around the school environment. Some students still do not understand the habit of washing hands with soap (CTPS), there is no implementation carried out in the Sd and it can also be said that knowledge and attitudes are still minimal regarding hand washing with soap (CTPS). This study aims to see the effect of audio-visual media on the knowledge and attitude of hand washing with soap that is good and right for students in grades III and IV. This research method uses Experimental Design with the "One Group Pretest Posttest Design" research design. A sample of 75 students was selected using a total sampling technique. The results of this study have increased by 69 students (92.0%) and student attitudes by 65 students (86.7%) in the good category. Based on the results of the non-parametric Wilcoxon Sign Rank Test, the p-value = 0.000 (p <0.05) is obtained, which means it shows the influence of audio-visual media on the level of knowledge and attitude of washing hands with soap that is good and right for students in grades III and IV at Yaspenhan Medan Marelan Elementary School. It can be concluded that there is a significant effect before (pretest) and after (posttest) given the intervention of animated hand washing with soap video. The advice is to conduct routine health education in collaboration with health facilities related to providing health education about Handwashing with Soap (CTPS) to increase students' knowledge and attitudes about the importance of good and correct hand washing.